2003
DOI: 10.1038/sj.onc.1207267
|View full text |Cite
|
Sign up to set email alerts
|

NGF activation of TrkA decreases N-myc expression via MAPK path leading to a decrease in neuroblastoma cell number

Abstract: In neuroblastoma (NB), expression of the TrkA receptor is correlated with good prognosis while N-myc amplification is correlated with poor prognosis. Decreased N-myc levels are key to controlling growth and inducing differentiation in NB cells. In this report, we detail mechanisms by which nerve growth factor (NGF) decreases N-myc levels in TrkA-transfected NB cells and its effect on NB cell proliferation. NGF induced a decrease in N-myc mRNA within 1 h of treatment that occurred in the presence of cycloheximi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 46 publications
1
14
0
1
Order By: Relevance
“…Nonetheless, Lucarelli et al (1997) showed that TrkA-transfected clones of N15 neuroblastoma cells exhibited a significant reduction in proliferation in response to NGF, while treatment of TrkB-transfected clones with BDNF had no effect. A decrease in neuroblastoma cell number was reported in another study from the same group, due to a TrkA-mediated decrease in N-myc expression (Woo et al, 2004). More recently, Kaplan and coworkers showed that virally mediated expression of TrkA induces apoptosis in two neuroblastoma cell lines, via a mechanism dependent on p53 and caspases (Lavoie et al, 2005).…”
Section: Trk-induced Death In Medulloblastoma and Neuroblastoma Cellsmentioning
confidence: 84%
“…Nonetheless, Lucarelli et al (1997) showed that TrkA-transfected clones of N15 neuroblastoma cells exhibited a significant reduction in proliferation in response to NGF, while treatment of TrkB-transfected clones with BDNF had no effect. A decrease in neuroblastoma cell number was reported in another study from the same group, due to a TrkA-mediated decrease in N-myc expression (Woo et al, 2004). More recently, Kaplan and coworkers showed that virally mediated expression of TrkA induces apoptosis in two neuroblastoma cell lines, via a mechanism dependent on p53 and caspases (Lavoie et al, 2005).…”
Section: Trk-induced Death In Medulloblastoma and Neuroblastoma Cellsmentioning
confidence: 84%
“…According to Eggert et al [21], expression of TrkA resulted in growth inhibition of the transfected cells compared to parental cells, whereas TrkB transfectants demonstrated an increased proliferation rate. Woo et al [8] detailed mechanisms by which NGF decreased N-myc mRNA levels in TrkA-transfected NB cells and reduced proliferation. Ho et al [22] provided in vitro evidence that the TrkB-BDNF pathway is associated with enhanced survival and resistance to chemotherapy in the NB cell line SH-SY5Y.…”
Section: Discussionmentioning
confidence: 98%
“…These pathways may provide attractive targets for the development of therapy aimed at inducing differentiation or programmed cell death in these tumors. There is evidence that retinoids [3][4][5], neurotrophins [6][7][8], and substances secreted by Schwann cells [9,10] are strong antiproliferative agents and play key roles for a good outcome in NB. However, experimental data about their relative performance to inhibit proliferation of NB cell lines as well as their possible additive effects and interactions are contradictory, with some works postulating synergistic [11], other antagonistic effects for the neurotrophin brain-derived neurotrophic factor (BDNF; Tebu-Bio/ Peprotech, Offenbach, Germany) and nerve growth factor (NGF; Tebu-Bio/Peprotech, Offenbach, Germany) [12].…”
mentioning
confidence: 99%
“…The most studied growth factor in NBL is nerve growth factor (NGF) which has a negative effect on NBL cell survival and growth. 3,4 In contrast, brain derived growth factor (BDNF) protects NBL from drug-induced apoptosis in vitro 5,6 and is associated with poor prognosis in NBL patients. 7 We have recently shown that insulin-like growth factor-I (IGF-I) signaling through its receptor (type I IGF receptor, IGF-IR) is altered and IGF-IR expression levels are increased in tumorigenic NBL cells.…”
Section: Introductionmentioning
confidence: 93%